Implications, contradictions and possibilities of open science in Spain: The case of REUNI+D - Adriana Gewerc-Barujel; Rocío Anguita-Martínez (Revista Latinoamericana de Tecnología Educativa)
This article reviews the state of open science as a scientific practice paradigm that is currently in the process of being implemented. It addresses the policies developed by the European Union and their specific implementation in Spain, as well as the discrepancies and barriers its adoption has posed for the Spanish university system. From here, the specific case of the REUNI+D Network is studied. This network comprises 14 educational research groups from 13 Spanish universities in their work from 2019 to the present. The activities and proposals carried out within this framework are described, and a questionnaire is used to identify the knowledge and perceptions of the network's members regarding open science and education, as well as the obstacles encountered. The results confirm that members have a clear understanding of what open science is and the opportunities it creates for collaboration, accessibility, and understanding the full life cycle of research. It highlights the need for training processes within the new framework. The final discussion emphasizes the difficulty of each higher education institution generating different policies and regulations on the subject, leading to contradictions in evaluation, and underscores the necessity of working with the three Cs (Coherence, Collaboration, and Coordination) for the development of open science.